Analisa Pemilihan Bahan Baku Kertas Daur Ulang Jenis Test Liner Di PT X - Nuruddin, Muchammad Ilham Ali; Nadliroh, Kuni (Jurnal Mesin Nusantara, 2022)
Although the world's forest resources have decreased, paper production has increased. Utilization of recycled fiber Recycle Fiber as a substitute for new fiber Virgin Fiber in production has a significant influence in the world of paper industri. In 2011 the world paper industri reached 403 million tons and about (53%) was produced from recycled paper. production of recycled fiber is cost competitive because the production cost is lower than Virgin Fiber's new fiber. Approximately (80%) of this type of paper comes from three sources, namely OCC Old Corrugated Containers, ONP Old Newspaper, and Office waste paper. (20%) of the used paper is removed from the ink which will be used as raw material for newsprint, tissue, white liner, or other types of white paper. Some of the raw materials for paper are used for paperboard, mineral cardboard. In the manufacture of paperboard, there is a type of Test Liner paper which is widely used as surface coating paper on cardboard.